O corpo que dança: metamorfoses de um corpo feminino - Sobreira, Alexandra Veras (2022)
This research was developed in the area of Psychology, more specifically, Critical Social Psychology, with an emphasis on dance, identity and metamorphosis. Belly dancing has a history crossed by different types of oppression of female bodies. Loaded with stigmas and prejudices that frame the dancer's performances in erotic and sensual senses, as a form of pleasure for heterosexual men. The research clipping is, however, referring to a branch of belly dancing, called Dark Fusion, a format that has adaptations and developments and carries influences from the Gothic style. Observing the reflection of representations in identity makes it possible to see all this construction based on colonialism, on gender and class relations, in the light of a decolonial perspective. The identity that emerges can be grouped as a fundamental piece for the understanding, acceptance and recognition of the invisibilities of marginal groups. It is a qualitative approach, with the narrative of a single life story about a woman who dances and her trajectory related to the dance process. Data analysis goes through the narrative, exposed by processes of metamorphosis and recognition intertwined with a process of listening to experiences, through interviews free of questionnaires and/or forms. A contextualized notion of identity based on Antônio Ciampa's studies of identity as a metamorphosis, and on the dynamics of the characters constituted by and about dance. The theoretical reference is the concept of "Orientalism", worked by Edward Said; decolonial criticisms from Ochy Curiel, María Lugones and Glória Anzáldua; and discussions about bodies by Merleau-Ponty, José Gil, and Uno. Research reiterates the approach of dance as a link to the vital force and instrument for several “selves” (characters), and field of experimentation of emotional depths. dance produces in the relationships of self-recognition and the senses experienced in the process of metamorphosis.